Being a parent of the sickest child: Malaysian perspectives - Wan Mohd Annuar, W Solihatul Hafidzah; Lee, Siew Pien; Makhtar, Aniawanis (Atlantis Press, 2021)
Mechanically ventilated children make up a small but growing segment of society's vulnerable population. The aim of the study was to understand the caring experiences of parents toward their mechanically ventilated children. This interpretive descriptive study was performed in the PICU of one tertiary hospital in Malaysia. The participants were purposively sampled. Semi-structured interviews were conducted with 21 parent caregivers of 18 children. Data were analysed by using Atlas.ti version 9. Thematic analysis was done and yielded the main theme, “The unpleasant experience in PICU” which emerged from two sub- themes: “The feeling of uncertainty” and “Recognizing the new child”. The study concluded that parents had fluctuating emotion throughout the stay. Positive parent-nurses interaction maintain the psychosocial health in embracing their journey.